Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Audit(StudiEmpiris Pada Auditor BPKP Perwakilan Jawa Tengah) - Khoisaroh, Riska, Dr. Triyono, S.E., M.Si (2017)
This research aimed to determine the factors of independency, integrity, objectivity, work experience, and competency on audit quality auditors in BPKP representatives of Central Java. The independents variable in this research were the independency, integrity, objectivity, work experience, and competency. Dependent variable was the quality of the audit. This research was a quantitative approach. The data is used primary data. Respondents in this research were auditors in BPKP representatives of Central Java. The sample is choosen using a convenience sampling and 72 respondents are used for the sample. The results of this research shows that (1) independency not effect on audit quality, (2) integrity effect on audit quality, (3) objectivity effect on audit quality, (4) work experience not effect on audit quality, and competency effect on audit quality.